A review of behaviour mechanisms between government and society in bargaining water pollution issues - Jiao, Yijuan; Tan, Mou Leong; Nooriah Yusof; Suriati Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2022)
Water pollution causes serious damage to people's lives, health and safety. As a prominent issue impacting social stability and development, protests to water pollution issues have become a great challenge for governments at all levels in recent years. This study aims to analyze the complex behaviour mechanism between participants and government, which is of great significance to the prevention and treatment of such incidents. This paper also discusses the cooperative and interactive relationship between government and society in the governance structure. In order to clarify the research progress of water pollution protest in the past decade, a systematic review has been used to identify 40 research papers related to social and governmental environmental negotiation mechanisms of water pollution events from the CNKI, SCOPUS, EIVL-LAGE2 and other databases. As a single management subject, a government can neither realize the efficiency and fairness of water resources allocation, nor effectively coordinate the contradictions among stakeholders such as the government, enterprises and the public. In order to protect the public's right to know, government must improve information disclosure, which also provides theoretical support for the government and relevant departments to control such events. Finally, the cooperative governance between government and society in water pollution events should be strengthened to improve the democratic governance ability of the government and achieve social governance innovation. Therefore, society-government cooperation should be taken as the breakthrough point, establish the concept of effective participation between government, enterprises and the public in the joint treatment of water pollution events. The study can be act as a reference for local authorities to better manage water pollution incidents with the public.